A method for producing polymer-encapsulated nanoparticles - Yunus, Robiah; Kalani, Mahshid (2011)
The present invention relates to a method for producingpolymer-encapsulated nanoparticles comprising the steps of: pumping supercritical fluid into a pressurised vessel, at a predetermined pressure; spraying a solution comprising a compound to be encapsulated, a polymer and an organic solvent into the vessel; collecting precipitated particles on a filter; and washing the particles with the supercritical fluid to remove residual solvent; characterised in that: the difference between the melting point of the polymer and the melting point of the compound to be encapsulated is not more than 10C.